2014
DOI: 10.1016/j.jpha.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Selective separation, detection of zotepine and mass spectral characterization of degradants by LC–MS/MS/QTOF

Abstract: A simple, precise, accurate stability-indicating gradient reversed-phase high-performance liquid chromatographic (RP–HPLC) method was developed for the quantitative determination of zotepine (ZTP) in bulk and pharmaceutical dosage forms in the presence of its degradation products (DPs). The method was developed using Phenomenex C18 column (250 mm×4.6 mm i.d., 5 µm) with a mobile phase containing a gradient mixture of solvents, A (0.05% trifluoroacetic acid (TFA), pH=3.0) and B (acetonitrile). The eluted compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Exposure of amisulpride to sunlight for 48 h resulted in 9.5 % degradation (Dabhi et al 2013 ). According to Talluri et al ( 2014 ), the solid state of zotepine was stable under white fluorescent light (after 72 h), while irradiation of solution caused 25 % degradation within 3 h. Zotepine in its solid state was more susceptible to sunlight (2.3 % degradation after 8 h). No degradation was observed in the case of olanzapine under UV-C irradiation (Shah et al 2008 ; Krishnaiah et al 2011 ), but according to another study (Pathak and Rajput 2009 ), this substance undergoes phototransformation in neutral, acidic, and basic solutions with creation of five photoproducts.…”
Section: Photostability Testing Of Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of amisulpride to sunlight for 48 h resulted in 9.5 % degradation (Dabhi et al 2013 ). According to Talluri et al ( 2014 ), the solid state of zotepine was stable under white fluorescent light (after 72 h), while irradiation of solution caused 25 % degradation within 3 h. Zotepine in its solid state was more susceptible to sunlight (2.3 % degradation after 8 h). No degradation was observed in the case of olanzapine under UV-C irradiation (Shah et al 2008 ; Krishnaiah et al 2011 ), but according to another study (Pathak and Rajput 2009 ), this substance undergoes phototransformation in neutral, acidic, and basic solutions with creation of five photoproducts.…”
Section: Photostability Testing Of Drugsmentioning
confidence: 99%
“…It is worth noting that irradiation of drug substances in solid state is sometimes an insufficient procedure. In such cases, a forced photodegradation study in solvent medium is recommended, for example, a photodegradation study of zotepine showed its stability under cool white fluorescence lamp radiation in solid state (0.1 % degradation after 72 h), while irradiation of zotepine solution led to rapid decomposition—25 % within 3 h with formation of the main degradation product (Talluri et al 2014 ) (Fig. 10 ).…”
Section: Photodegradation Studies On Psychotropic Drugsmentioning
confidence: 99%
“…Obecnie najnowsze wytyczne wskazują, że wszelkie nieznane zanieczyszczenia, zaobserwowane na każdym etapie rozwoju procesu produkcji, w trakcie wykonywania testów wymuszonej degradacji lub przy regularnych badaniach stabilności, są izolowane i analizowane za pomocą różnych technik chromatograficznych, mianowicie wysokosprawnej chromatografii cieczowej (HPLC), chromatografii cienkowarstwowej (TLC), chromatografii gazowej (GC), elektroforezy kapilarnej (CE), chromatografii kationowymiennej (CEC), chromatografii z eluentem w stanie nadkrytycznym (SFC). W przypadku pojawienia się trudności z izolacją produktów degradacji w czystej postaci, są stosowane takie techniki jak HPLC-DAD, LC-MS, LC--NMR oraz chromatografia gazowa sprzężona ze spektrometrią mas (GC-MS) [40][41][42][43].…”
Section: Nowa Strategia Badań Fotostabilnościunclassified
“…Hence, the aim of the present study was to investigate the degradation behavior of PRCLD under various stress conditions using RP-HPLC and characterize [8][9][10][11][12][13][14][15][16][17] all DPs and as well as process impurities using LC/ESI/QTOF/MS/MS.…”
Section: Introductionmentioning
confidence: 99%